Gambaran Tingkat Nyeri Pada Pasien Post Sectio Caesarea Metode Eracs di RS H.A Zaky Djunaid Pekalongan - Qoniatul Ainiyah; Ratnawati Ratnawati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Physiological processes such as pregnancy, labor and birth can be difficult and can occur at any time, and can have serious impacts on the mother and fetus. So the SC ERACS method of delivery is an option. ERACS is a SC delivery technique that is becoming increasingly popular in society, especially among pregnant women because it can shorten recovery time after surgery and reduce post-operative pain. This study aims to describe the level of pain in patients post caesarean section using the ERACS method. This research is a quantitative descriptive study, data collection using accidental sampling techniques, namely all SC ERACS patients at H.A Zaky Djunaid Hospital for 1 month, namely 52 respondents. This research instrument uses NRS. The data analysis used is univariate in the form of a frequency distribution. The results showed that the characteristics of the respondents were mostly in the early adulthood category, namely aged 26-35 years, 27 respondents (51.9%), 34 respondents (65.4%) respondents who did not work, 24 respondents (46.2) who indicated a history of SC, and 41 respondents (78.8%) were multiparous. The pain level of post-SC patients using the ERACS method, the majority of mothers experienced mild pain on a scale of 1-3, 47 respondents (90.4%). The conclusion that can be drawn is that the pain level of post-SC patients using the ERACS method is that most mothers experience mild pain.